Influence Of Mid-Cycle Pg Therapy On Fertility And Plasma Profile Of Progesterone And Biochemical Constituents In Repeat Breeding Cows And Buffaloes - Nakrani, B.B.; Dhami, A.J.; Hadiya, K.K.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted under field conditions in Amul and Panchamrut milk-shed areas of Gujarat on 30 postpartum cows and buffaloes each of average body condition score without any visible or palpable genital abnormalities. These comprised of 20 repeat breeding (10 PG treated and 10 untreated control) and 10 normal cyclic control animals in each class. The aim was to evaluate and compare the fertility response as well as plasma progesterone and biochemical profile of repeat breeders to i/m injection of PGF2α 25 mg at mid-cycle with fix timed AI (FTAI) twice 72 and 96 hrs later (Gr-I), with those of untreated repeat breeder (Gr-II) and normal cyclic (Gr-III) controls. The oestrus induction response obtained with mid-cycle PG treatment in both cows and buffaloes was 100 % within mean intervals of 53.79±2.18 and 61.16±5.21 h, respectively, from the day of PG injection. The conception rates at induced/first oestrus and overall of 3 cycles in cows were 50 and 70%, and in buffaloes 60 and 70.00 %, respectively. The corresponding first service and overall conception rates in untreated repeat breeder cows were 20 and 30 % and buffaloes 20 and 40 %, respectively, and in normal cyclic control cows 50 and 80% and in buffaloes 40 and 70%. The repeat breeding cows and buffaloes had significantly (P
Keywords: Repeat breeding; Cow; Buffalo; PGF2α treatment; Conception rate; Progesterone profile